An Explanation of Job Satisfaction in School Principals Based on their Performance of the Position - Inmaculada MARTÍNEZ GARCÍA; Javier GIL FLORES (Ediciones Universidad de Salamanca, 2018)
School management and pedagogical leadership are key in the improvement of the quality of schools. It is vital to people in charge to be satisfied with their performance of the position, a fact that leads to a greater motivation and commitment. In this paper we study job satisfaction of principals in secondary schools, given the importance of educational agents for the proper running of schools. To this end, a secondary data analysis is carried out based on data obtained in the latest edition of the Teaching and Learning International Survey (TALIS) study promoted by the OECD (OECD, 2014) with the aim of explaining satisfaction in the school management related to variables associated to the performance of the role. The results show a greater satisfaction of principals when they allow the community to participate in the decision making process, when they perform a distributed leadership and promote a collaborative culture. Among the tasks related to job dissatisfaction are those linked to the traditional bureaucratic management model still prevailing. Based on the results, there have been made some proposals based on the development of professional management paths and training in skills related to distributed leadership, the promotion of collaboration spaces between educational agents and learning communities.